Correlation between Magnetic Resonance (MR) Volumetry and Apparent Diffusion Coefficient (ADC) Value of Hippocampal Formation in Medically Intractable Temporal Lobe Epilepsy - Amran, Mohd Hanif (2018)
Objective: The purpose of this study is to determine volumetry values of the Hippocampal Formation in refractory Temporal Lobe Epilepsy patients comparing with volumetry values of normal individual, correlating the volumetry values with ADC (Apparent Diffusion Coefficient) values for detecting hippocampal formation abnormalities in patients with medically intractable temporal lobe epilepsy (MITLE). Other than that is to correlate MR volumetry values with duration of illness in refractory Temporal Lobe Epilepsy (TLE) patients. Background: In this study, we compared the hippocampal volume of patients with underlying medically intractable temporal lobe epilepsy (MITLE) and normal subjects and to look for correlation between the hippocampal volume, ADC values and duration of illness. Methodology: A total of 28 participants were recruited for the present study; there were 14 participants in control and TLE-positive group, respectively. MR images were evaluated for hippocampal volumetric calculation and was correlated with ADC maps and duration of illness. Mean and SDs were obtained for each measurement, and level of significance was determined. Analysis of mean volumetry, ADC values were performed using PASW version 18. We used an independent t-test to investigate group differences in mean hippocampal volumetric value. Pearson correlation was used to examine relationships between mean hippocampal volumetric value and duration of illness, also as mean hippocampal volumetric value with ADC value. Results: There was no significant difference shown between the left and right hippocampal MR volumetric values in the control group. However, significant differences were shown in hippocampal MR volumetric values, were found between control and TLE-ipsilateral sites. There are also significant differences were shown in hippocampal volumetric values, were found between both sides of hippocampus in right and left TLE patients. The hippocampal MR volumetric values did not show significant correlation with the duration of illness. There was significant correlation between hippocampal volumetric value and ADC. Conclusions: Hippocampal volumetry have the capabilities to detect changes in the hippocampal formation and to lateralize the seizure focus in patients with TLE. There is no significant correlation between hippocampal volumetric values with duration of illness. There was significant correlation between hippocampal volumetric values with ADC.